Influence of confluent marine currents in an ecotonal region of the South-West Atlantic on the distribution of larval anisakids (Nematoda: Anisakidae) - Lanfranchi, Ana Laura; Braicovich, Paola Elizabeth; Cantatore, Delfina María Paula; Irigoitia, Manuel Marcial; Farber, Marisa Diana; Taglioretti, Verónica; Timi, Juan Tomas (Parasites & Vectors)
Background: In the marine environment, transitional zones between major water masses harbour high biodiversity, mostly due to their productivity and by containing representatives of species characteristic of adjacent communities. With the aim of assessing the value of larval Anisakis as zoogeographical indicators in a transitional zone between subtropical and sub-Antarctic marine currents, larvae obtained from Zenopsis conchifer were genetically identified. Larvae from Pagrus pagrus and Merluccius hubbsi from two adjacent zoogeographical provinces were also sequenced. Results: Four species were genetically identified in the whole sample, including Anisakis typica, A. pegreffii, A. berlandi and a probably new species related to A. paggiae. Anisakis typica and A. pegreffii were identified as indicators of tropical/subtropical and sub-Antarctic waters, respectively, and their presence evidenced the transitional conditions of the region. Multivariate analyses on prevalence and mean abundance of Anisakis spp. of 18 samples represented by 9 fish species caught south of 35°S determined that host trophic level and locality of capture were the main drivers of the distribution of parasites across zoogeographical units in the South-West Atlantic. Conclusions: Most samples followed a clear zoogeographical pattern, but the sample of Z. conchifer, composed mostly of A. typica, was an exception. This finding suggests that population parameters of A. typica and A. pegreffii could differ enough to be considered as a surrogates of the identity of larvae parasitizing a given host population and, therefore, a step forward the validation of the use of larval Anisakis as biological indicators for studies on host zoogeography. Fil: Lanfranchi, Ana Laura. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mar del Plata. Instituto de Investigaciones Marinas y Costeras. Universidad Nacional de Mar del Plata. Facultad de Ciencias Exactas y Naturales. Instituto de Investigaciones Marinas y ...